Respon Israel atas instabilitas konstalasi politik dan militer Timur Tengah: Perspektif realisme defensif - Shori, Alam An; Wahid, Muhammad Aqil (Maliki Interdisciplinary Journal, 2024)
The Middle East has succeeded in becoming a focal point of international politics. It is the cradle of many great world civilizations, including ancient Egyptian, Mesopotamian, Persian, and Islamic civilizations. This study adopts a qualitative descriptive approach, using the defensive realism political analysis method from Stephen Waltz's perspective. The research data comes from various sources such as news, official websites, books, and scientific journals. The data pertains to information relevant to the object of study. This type of research is often referred to as Library-based Research. The data is collected by reviewing information and news related to Israel's Balance of Threat in Middle Eastern politics and is then documented. Data analysis is conducted using Miles and Huberman's techniques, which include (1) data reduction, (2) data presentation, and (3) drawing conclusions. The study concludes that Israel possesses the military, economic, political, and diplomatic capabilities to address potential threats from Arab countries. Israel's military strength ensures its defense, and the nation is also equipped with advanced technological capabilities, both in civil and military sectors. The study also reveals that, in addressing these threats, Israel prioritizes balancing over bandwagoning, reflecting its strong confidence in its national capabilities.